(untitled) (Research, Society and Development, 2020)
Objective: To report the experience of undergraduate nursing students at the Universidade Federal Fluminense (UFF) on the organization of the work process in the bandage sector in primary care. Methodology: Research of the type of experience report based on the experience of nursing students at a Public University about the work process of nurses in the bandage sector of a Regional Polyclinic in the city of Niterói-RJ. The practice took place in the first half of 2019. The object, agents, instruments, purpose, methods and products, components of the work process were taken into account. Results and discussion: It was observed that the completion of each stage of the work process is carried out by nursing professionals in the hospital sector, in search of the best clinic and patient safety as the final product. The sector is run by a nurse, whose work includes planning, communication, qualified assistance, teaching, research and ethical relationships. Therefore, it is emphasized that good nursing-technical, nursing-patient communication, a practice that comprehensively addresses each step of the work process and is based on evidence, ensures differentiated, assertive care and the final product is patient safety. Final considerations: The present study contributed to the formation of the learning of the academics involved with regard to the work and management process. The performance of the nurse manager is directly related to the good functioning of a sector, given its autonomy and qualification for the work performed, and this object of study in its formation.